Synthesis and in vitro activity of platinum containing 2‐oxazoline‐based glycopolymers. Issue 18 (9th July 2014) - Tauhardt, Lutz; Pretzel, David; Bode, Stefan; Czaplewska, Justyna A.; Kempe, Kristian; Gottschaldt, Michael; Schubert, Ulrich S.
ABSTRACT We report the synthesis of glyco(poly(2‐oxazoline)s) functionalized with Pt(II) units for targeted tumor applications. To this end, poly(2‐ethyl‐2‐oxazoline‐block‐2‐(3‐butenyl)‐2‐oxazoline) is modified with thiol‐modified acetyl protected glucose and galactose, respectively, and terpyridine (tpy) units using thiol‐ene photoaddition. Deprotection of the sugars with sodium methoxide and treatment with Pt(COD)Cl2 applying a mild synthesis route yields polymers with monosaccharide targeting moieties and cytotoxic Pt(II) units. The polymers and intermediates are characterized by 1H nuclear magnetic resonance spectroscopy and size exclusion chromatography. Subsequently, the hemolytic activity, induction of erythrocyte aggregation as well as the cytotoxicity against mouse fibroblast L929 cells, human embryonic kidney cells HEK 293, and human hepatocytes HepG2 are studied. The comparison to cisplatin, the standard for cancer therapy, demonstrates the potential of the presented system. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 2703–2714